Pengembangan Kewirausahaan Siswa Sejak Dini Melalui Keterampilan Aksesoris Manik Pada Siswa Kelas V SD Negeri 24 Kota Bengkulu - Triasleni, Elza Septi; Irwanto, Tito; Anggriani, Ida; Febliansa, Muhammad Rahman; Sari, Desti Rupita (Universitas Dehasen Bengkulu, 2024)
This Community Service aims to provide knowledge of the efforts made in developing an entrepreneurial spirit from an early age through bead accessories skills in class 5D at SD Negeri 24 Bengkulu city. Entrepreneurship is an important skill and attitude to face future challenges, especially in the world of business and entrepreneurship. The results of the outreach showed a significant increase in students' level of understanding about entrepreneurship development from an early age through bead accessory skills. Students have responded and are interested in starting a business while studying at a higher level. The method of this activity is the socialization of providing materials and making skills from beads which are made into bracelets, phone straps and rings which are directly practiced and taught to students in class 5D at SD Negeri 24 Bengkulu City. Thus, this report contributes to the development of student entrepreneurship education from an early age and increases students' entrepreneurial abilities through bead accessory skills. The students' response to the implementation of the activity of making bead accessories skills was very good.